Choice of Heuristic Strategies with Respect to Age - Eisenmann, Petr; Přibyl, Jiří; Novotná, Jarmila; Břehovský, Jiří; Cihlář, Jiří (Scientia in educatione, 2017)
The paper reports on an experiment that was a part of a longitudinal research project entitled Development of culture of problem solving in mathematics carried out in Czech schools. The experiment involved 584 respondents aged 11–17. The experiment maps the distribution in pupils’ selection of heuristic strategies towards solving mathematical problems in case of different age groups of pupils. Pupils from the 6th and 8th grades of lower secondary and the Ist and IIIrd grade of upper secondary school were assigned three problems that could be solved effectively using heuristic strategies. Besides the success rate in solving the problems, attention was also paid to the manner in which the pupils managed to solve them. The results of the experiment show that the pupils tended to use some particular heuristic strategies despite the fact that they had not come across them in lessons. The occurrence of some of these strategies is independent of the age of pupils.